Security in Ad-hoc and Sensor Networks First European Workshop, ESAS 2004, Heidelberg, Germany, August 6, 2004, Revised Selected Papers - Castelluccia, Claude; Hartenstein, Hannes; Paar, Christof; Westhoff, Dirk (Computer Communication Networks and Telecommunications, 2005)
Ad hoc and sensor networks are making their way from research to real-world deployments. Body and personal-area networks, intelligent homes, environmental monitoring or inter-vehicle communications: there is almost nothing left that is not going to be smart and networked. While a great amount of research has been devoted to the pure networking aspects, ad hoc and sensor networks will not be successfully deployed if security, dependability, and privacy issues are not addressed adequately. As the first book devoted to the topic, this volume constitutes the thoroughly refereed post-proceedings of the First European Workshop on Security in Ad-hoc and Sensor Networks, ESAS, 2004, held in Heidelberg, Germany in August 2004. The 17 revised full papers were carefully reviewed and selected from 55 submissions. Among the key topics addressed are key distribution and management, authentication, energy-aware cryptographic primitives, anonymity and pseudonymity, secure diffusion, secure peer-to-peer overlays, and RFIDs.